2002
DOI: 10.1128/jvi.76.9.4591-4602.2002
|View full text |Cite
|
Sign up to set email alerts
|

Rafts Promote Assembly and Atypical Targeting of a Nonenveloped Virus, Rotavirus, in Caco-2 Cells

Abstract: Rotavirus follows an atypical pathway to the apical membrane of intestinal cells that bypasses the Golgi. The involvement of rafts in this process was explored here. VP4 is the most peripheral protein of the triple-layered structure of this nonenveloped virus. High proportions of VP4 associated with rafts within the cell as early as 3 h postinfection. In the meantime a significant part of VP4 was targeted to the Triton X-100-resistant microdomains of the apical membrane, suggesting that this protein possesses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
83
1

Year Published

2005
2005
2010
2010

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(93 citation statements)
references
References 71 publications
9
83
1
Order By: Relevance
“…In these cells, both rotavirus and Hsp70 are released before any detectable cell lysis, through an atypical pathway involving lipid rafts (3,21,35). In the present work, we found that the Hsp70 level rapidly increases in response to rotavirus infection in Caco-2 cells and that this virus stress induction is specific to the molecular chaperone Hsp70.…”
Section: Viral Infections Of Mammalian Cells Often Results In Alterationssupporting
confidence: 56%
“…In these cells, both rotavirus and Hsp70 are released before any detectable cell lysis, through an atypical pathway involving lipid rafts (3,21,35). In the present work, we found that the Hsp70 level rapidly increases in response to rotavirus infection in Caco-2 cells and that this virus stress induction is specific to the molecular chaperone Hsp70.…”
Section: Viral Infections Of Mammalian Cells Often Results In Alterationssupporting
confidence: 56%
“…50,51) A rotavirus follows an atypical pathway to the cell membrane by the way of the Golgi apparatus. A direct interaction of VP4, which is the most peripheral protein of the triple-layered structure of a rotavirus, with lipid rafts promotes assembly and atypical targeting of the rotavirus in intestinal cells.…”
Section: Role Of Lipid Rafts In Virus Assembly And/or Buddingmentioning
confidence: 99%
“…The role of membrane rafts in the intracellular assembly of nonenveloped viruses has been reported only for rotavirus [29,[138][139][140][141] and bluetongue virus [142], belonging to the family Reoviridae. Rotavirus replication occurs in large inclusions (known as viroplasm) in the cell cytoplasm, where viral RNA is replicated and double-layered particles are assembled.…”
Section: Role Of Membrane Rafts In Virus Genome Replication Assemblymentioning
confidence: 99%
“…In this process, the involvement of transient enveloped particles with rafts is highly questionable since rafts are thought to be absent from the ER. Association of VP4 with rafts in the extrareticular compartment promotes rotavirus morphogenesis as a final assembly platform and apical targeting toward the release process [29,138,139], which are significantly dependent on the raft heterogeneity (the nature and proportion of phospholipids and glycosphingolipids) [140]. Moreover, NSP4 undergoes Golgi networkspecific processing for its N-glycans through caveola-dependent Golgi network-bypassing transport [141].…”
Section: Role Of Membrane Rafts In Virus Genome Replication Assemblymentioning
confidence: 99%
See 1 more Smart Citation